ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA MENGGUNAKAN MS. ACCESS PROGRAMMING - Suhartono, . (www.bsi.ac.id, 2015)
For many companies, the sources and uses of working capital is an important thing because in addition to meet the working capital operating companies can also be used for investment . There are many sources of working capital such as net income, the sale of non-current assets, sale of shares / bonds, borrowing funds from banks and credit from suppliers. The benefits of working capital, among others, allows the company to pay all obligations on time, allowing it to have a supply of goods in an amount sufficient to serve the consumer and allows the company to operate more effectively because there is no difficulty to obtain goods or services required . While the purpose of working capital, among others, to meet the liquidity needs of the company, to maximize the use of current assets to increase sales and profits and to protect the company in the event of a crisis due to the falling value of the working capital current assets. It is necessary for a proper analysis of the sources and uses of working capital in the company's decision-making process using MS Access Programming Keywords: Sources, Use of Working Capital, Ms. Access Programming